Evaluation of the Validity and Usability of the Mobile Application for Early Detection of Metabolic Syndrome: A Cross-Sectional Study - Purwanti, Okti Sri; Diaz Aziz Pramudita; Agus Sudaryanto; Tanjung Anita Sari Indah Kusmaningrum; Syarif Fathurozaq Wibowo; Ulfa Munawaroh Diniyah; Muhammad Hananfajri Rasyid; Danar Wasis Pambudi; Annisa Niken Larasati; Nimas Zuhrufana (Universitas Muhammadiyah Surakarta, 2026)
Metabolic syndrome is a cluster of risk factors for cardiovascular disease and type 2 diabetes mellitus in adults. The development of a health application-based instrument is important. This study aims to evaluate the Content Validity Index (CVI) and System Usability Scale (SUS). This study used a cross-sectional study design. Content validity was analyzed using the Content Validity Index (CVI) method involving five experts. Researchers evaluated the usability of the application using the System Usability Scale (SUS) and tested it on nine users. Researchers analyzed the data descriptively to obtain CVI and SUS scores. The test results showed that the I-CVI value was 1.00 and the S-CVI/Average was 1.00, indicating that all items in the application were highly relevant. The SUS score was 76.11, and the application was categorized as acceptable (good), indicating that the application was easy to use and well received by users. This mobile application has excellent content validity and good usability, making it suitable for use as an early detection instrument for metabolic syndrome. This application has the potential to support health promotion and prevention efforts to reduce non-communicable diseases in the community